Effect of modeling liquids on resin composite roughness and color parameters after staining and toothbrushing - Thaís Souza MAIA; Thamires Diogo LIMA; Vanessa Miranda RAMOS; André Luís FARIA-; Murilo de Sousa MENEZES (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This study evaluated surface roughness, color stability, whitening index, and opacity of different types of modeling liquids for resin composite coating after exposure to staining and toothbrushing. Disc-shaped resin composite (Vittra APS, FGM) specimens were fabricated and divided into four groups (n = 10 each): control group, Composite Wetting resin (Ultradent Products), Adper Scotchbond Multipurpose adhesive (3M ESPE), and Adper Universal adhesive (3M ESPE). Surface roughness (Ra) was measured using a rugosimeter, while color stability (∆E00), whitening index (WI), and opacity (%) were measured using a spectrophotometer. Assessments were made at four time points: after polishing (baseline, T1), after immersion in red wine for 24 h (T2), and after 5,000 (T3) and 10,000 (T4) cycles of toothbrushing. Scanning electron microscopy images were captured to analyze the scratches created. The data were statistically analyzed by two-way repeated-measures analysis of variance and Tukey's honestly significant difference tests (α = .05). Modeling with the Wetting resin resulted in higher surface roughness (p < 0.05) and low color stability, which were attributable to porosities. Higher color change values were observed in the control group after staining. Both adhesives showed the lowest mean ΔE00 values (p < 0.005). WI decreased after staining, except with the use of the Universal adhesive (p < 0.005). The lowest opacity values were observed at baseline for all groups (p < 0.005). The Universal and Scotchbond adhesives had lower surface roughness, better color stability, higher WI, and the lowest opacity values after staining with red wine and toothbrushing.